Histidine146 of Human Serum Albumin Plays a Prominent Role at the Interface of Subdomains IA and IIA in Allosteric Ligand Binding - Kaneko, K.; Chuang, Victor; Minomo, A.; Yamasaki, K.; Bhagavan, N.; Maruyama, T.; Otagiri, M. (Wiley, 2011)
Fatty acids are endogenous ligands of human serum albumin (HSA) that induce conformational changes and participate in allosteric ligand binding to HSA. In a previous study, we showed that, when myristate (MYR) is present, the binding of [14C]ketoprofen (KP) to subdomain IA of HSA was increased, indicating that, when MYR binds to HSA, a new binding site in formed in that region. Meanwhile, an N-B transition has been reported to increase the binding of ligands at alkaline pH when the status of albumin is the B-conformer. Six histidine single mutants of HSA, H9A, H39A, H67A, H105A, H128A and H146A were produced and photolabeled with [14C]KP at pH 6.5, 7.4 and 8.2 and the role of each histidine in causing the N-B transition induced allosteric ligand binding was examined. Cyanogen bromide cleavage of the photolabeled native HSA showed that subdomain IA was the site of the allosteric binding of KP at pH 8.2.From the photolabeling results, H146 was found to play a prominent role whilst H128 played little or no role in the allosteric binding. However, the remaining 4 mutants did not show a clear photolabeling pattern that was similar to either native HSA or H146A and, as a result, no firm conclusions can be made. An additional histidine mutant, H146I, was produced to confirm the results for H146A. A similar experiment using H146I showed that a benzene ring-like structure at position 146 is required for the allosteric ligand binding to occur.